2021
DOI: 10.3390/biom11111594
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-Methyltransferase in Head and Neck Tumors: A Comprehensive Review

Abstract: The head and neck tumors (HNT) are a heterogeneous group of diseases ranging from benign to malignant lesions, with distinctive molecular and clinical behaviors. Several studies have highlighted the presence of an altered metabolic phenotype in HNT, such as the upregulation of nicotinamide N-methyltransferase (NNMT). However, its biological effects have not been completely disclosed and the role of NNMT in cancer cell metabolism remains unclear. Therefore, this comprehensive review aims to evaluate the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
(95 reference statements)
1
21
0
Order By: Relevance
“…Our research revealed that NNMT expression was significantly variable in 24 types of tumors and paracancerous tissues, and up-regulated in nine types of malignancies, which was consistent with the immunohistochemical analysis of protein levels. The results of PAAD (Xu et al, 2016), STAD (Chen et al, 2016), KIRC (Reustle et al, 2022), GBM (Palanichamy et al, 2017), HNSC (Togni et al, 2021) and COAD (Ogawa et al, 2022) were similar to previous studies. However, the results suggested that there was a relatively high level of NNMT expression in the normal tissues of 15 distinct types of tumors, which may be a result of the vast variation in metabolic status between tumor types (Park et al, 2020;Hanahan, 2022).…”
Section: Figure 14supporting
confidence: 89%
“…Our research revealed that NNMT expression was significantly variable in 24 types of tumors and paracancerous tissues, and up-regulated in nine types of malignancies, which was consistent with the immunohistochemical analysis of protein levels. The results of PAAD (Xu et al, 2016), STAD (Chen et al, 2016), KIRC (Reustle et al, 2022), GBM (Palanichamy et al, 2017), HNSC (Togni et al, 2021) and COAD (Ogawa et al, 2022) were similar to previous studies. However, the results suggested that there was a relatively high level of NNMT expression in the normal tissues of 15 distinct types of tumors, which may be a result of the vast variation in metabolic status between tumor types (Park et al, 2020;Hanahan, 2022).…”
Section: Figure 14supporting
confidence: 89%
“…Several metabolites indeed represent cofactors, substrates or competitive inhibitors of epigenetic enzymes. For example, mutations in isocitrate dehydrogenase (IDH) and overexpression of nicotinamide N-methyltransferase (NNMT) enzymes occur in cancers, including HNSCC, promoting cancer progression and chemoresistance, and induce alterations in DNA and histone methylation profiles [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Epigenetics In Cancermentioning
confidence: 99%
“…The physiological role of NNMT is to utilize S-adenosyl-L-methionine (SAM) to transfer methyl to nicotinamide (NAM), producing 1-methylnicotinamide (1MNA) and releasing S-adenosyl-L-homocysteine (SAH) [ 12 , 13 ]. Currently, the analysis of proteomic data has revealed that NNMT is expressed in various cancer types, including breast cancer [ 14 ], bladder cancer [ 15 ], gastric cancer [ 12 , 16 ], liver cancer [ 12 ], colorectal cancer [ 17 ], ovarian cancer [ 18 ], oral squamous cell carcinoma [ 19 ], and skin cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%